Question: question on assume vs. assuming

from help, it says 

The expression assuming property calling sequence evaluates the expression under the assumption property on all names in expression.

Then why 

restart;
expr := Sum((-1)^n - 1, n = 1 .. infinity):
simplify(op(1,expr)) assuming n::even;

does not simplify expr to zero, while

restart;
expr := Sum((-1)^n - 1, n = 1 .. infinity):
assume(n::even):
simplify(op(1,expr))

does simplify expr to zero.


I would have expected both to give zero. 

 

Please Wait...